ANALISIS PENGARUH KUALITAS PRODUK, HARGA, LOKASI DAN KUALITAS PELAYANAN TERHADAP MINAT BELI ULANG KONSUMEN (Studi pada Warung Makan “Bebek Gendut” Semarang) - Faradiba Faradiba; Sri Rahayu Tri Astuti (Faculty of Economics and Business Diponegoro University, 2013)
This study aims to determine how much influence the quality of product, price, location, and quality of service to repurchase intention. The problem that facing by Bebek Gendut Semarang is income which decreasing, caused many new restaurans. And this research also aims to analyze the most dominant factors that influence on repurchase intention of Bebek Gendut Semarang.The population in this study are customers of Bebek Gendut Semarang. Samples were taken of 100 respondents using a purposive sampling technique. Data was collected using a survey method through questionnaires filled out by customers. Then, the data obtained were analyzed using multiple regression analysis. This analysis includes the validity test, reliability test, multiple regression analysis, classic assumption test, hypothesis testing through the t test and F test, and coefficient of determination analysis (R²). From the analysis result, the indicators in this study are valid and reliables. The most dominant factor that influence on repurchase intention is quality product follow by the location, then quality service and price. Then the F Test can be seen that the independent variables feasible to test the dependent variable. The result of Adjusted R Square is 0,498 it means that independent variable can explain about 49,8% of dependent variable.